General approach to the line source electromagnetic scattering by a circular strip: Both E‐ and H‐polarisation cases - Karaçuha, Kamil (Institution of Engineering and Technology (IET), 2021)
Abstract This study presents a new approach to line‐source diffraction by a circular strip. The investigation is obtained by employing both electric and magnetic line sources where the corresponding field components satisfy the Dirichlet and Neumann boundary conditions. The position of the line source in the problem resulted in a very different radiation mechanism. Regarding the boundary condition and the aperture size, the total field characteristics change noticeably. The current density on the circular strip is expressed by Fourier series expansion, and then, orthogonal polynomials including edge condition are utilised to obtain the scattered field. The investigation is done throughout the far‐field radiation pattern, near‐field distributions, and the total radar cross‐section. Then, the results are compared with the analytical and numerical outcomes. For the comparison, the method of moments and the method of auxiliary sources are employed as the numerical tools.
Keywords: QC501-766; Dirichlet boundary condition; Neumann boundary condition; diffraction; TK5101-6720; circular strip; Electricity and magnetism; resonance; Telecommunication; line source